Is Barrett Equation Universally Applicable for Explaining Dielectric Constant of Ferroelectrics and Ferroelectric Thin Films? - Lahiry, S. (Journal of Scientific Research, 2024)
Slater’s formula for perovskite ferroelectrics was modified by Barrett to include the quantum effect. Dielectric constant vs temperature (e¢ vs. T) data for Strontium titanate (ST) and Potassium tantalate (KT) in single crystals and ceramics fitted well, while the data (e¢ vs. T) for Barium titanate (BT) in single crystals and ceramics did not fit at all to Barrett’s equation. That is, ferroelectrics like ST, which show only Curie-Weiss temperature but does not show a ferroelectric transition, obey Barrett’s equation. The Curie-Weiss law fitted the data of BT well. That KT a cubic and consequently a paraelectric down to 13 K obeys Barrett’s equation is intriguing. e¢ vs T values of Barium strontium titanate (BaxSr1-xTiO3), thin films could be fitted to the Curie-Weiss law, thus eliminating the existence of quantum effect in thin films.